Use of Active Carbon Produced by Hydrothermal Method from Agricultural Waste in Methylene Blue Removal - Boyrazli, Mustafa; Öztürk, Elif Arancı; Çelik, Emrah; Yaslı, Mehmet Ali (My University, 2024)
In this study, the use of activated carbon produced from agricultural waste via the hydrothermal method for the removal of methylene blue from solution was examined. Pistachio roasting facility waste was selected as the agricultural waste. For activated carbon production, carbonized products were treated in a hydrothermal device in the presence of an activator for various durations. During processes conducted at a constant temperature, high pressure was achieved, allowing the activated carbon to attain a high adsorption capacity. The results showed that the sample with a KOH impregnation ratio of 1:1, treated in a hydrothermal device for 480 minutes at 160 °C, was able to remove methylene blue with a 99.85% extraction yield in a solution with a 350 ppm methylene blue concentration.
Keywords: Adsorption; Activated Carbon; Methylene Blue; Pistachio; Hydrothermal Carbonization; Organic Waste